Hooked in Seconds: How Content Quality and Engagement Trigger Gen Z’s Impulse Buying Online - Chelsea Patricia Suryanto; Dewi Mustikasari Immanuel (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study discusses how the experience of watching short video content influences the dimensions of digital content experience, namely entertainment, education, escapism, and esthetic on pleasure that will impact online impulsive buying behavior among Generation Z consumers. With the continued growth of the short video business, it is crucial to understand how visual, educational, and entertaining content affects consumer emotions. This study uses a quantitative research design with a structured online survey that was distributed to 389 Generation Z respondents aged 18–28 years. The measurements consisted of six constructs: Entertainment Experience, Educational Experience, Escape Experience, Esthetic Experience, Pleasure, and Online Impulsive Buying, which were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all dimensions of digital content experience significantly increase pleasure, with Esthetic Experience having the strongest effect, followed by Educational, Entertainment, and Escape Experiences. Satisfaction, in general, acts as a strong mediator in linking the experience of enjoying content with online impulsive buying behavior. Furthermore, pleasure has a strong and significant effect on online impulsive buying behavior, indicating a central role in translating content experience into purchasing. These findings suggest that Generation Z's impulsive buying is primarily driven by emotional responses formed through visually attractive, informative, and entertaining content generated by short video content that is visually and educationally appealing.